Closing the Loop: Enhancing Local Monitoring of Child Poverty to Leave No Child Behind - Pablo de la Rasilla; Iraklis Stamos; Paola Proietti; Alice Siragusa (MDPI AG, 2024)
Research on the Leave No One Behind principle of the Sustainable Development Goals (SDGs) within the context of the Agenda 2030 is currently prevalent; however, research on monitoring child poverty at the sub-national (local) level is still limited. This paper addresses this gap by examining indicators developed for monitoring the phenomenon at different territorial levels (global, European, and national) and assessing their territorial transposition locally, using the city of Cadiz, Spain, as a case study. Interviews with local stakeholders reveal that despite the availability and access to related indicators and data, relevant actors must enhance their efforts to utilize such indicators effectively. Based on desktop research and qualitative analysis, the paper delivers recommendations for improving local monitoring of child poverty in Europe and inducing policy changes. This knowledge can inform targeted interventions, policy formulation, and resource allocation to tackle child poverty and promote equitable and inclusive societies.